The Role Of KKN Students In Increasing Environmental Awareness To Maintain Cleanliness Of Talang Perapat Village Roads, West Seluma District - Angga, Angga; Prayuda, Angga Ares; Fenti, Fenti; Ayu, Hesi Putri; Yanti, Rina Trisna; Soleh, Ahmad; Gayatri, Ida Ayu Made Er Meytha (Universitas Dehasen Bengkulu, 2025)
This study aims to describe the implementation and impact of a waste bank The Community Service Program (Kuliah Kerja Nyata/KKN) is one form of student dedication to society, where students apply the knowledge and skills they have acquired during their studies. This activity aims to assist the community while supporting the implementation of the Tri Dharma of Higher Education. This study aims to describe the role of KKN students in raising awareness of road cleanliness in Talang Perapat Village, Seluma Barat District. The research method used is descriptive qualitative with data collection techniques including interviews, participatory observation, and documentation. The results of the study show that KKN students successfully increased residents’ awareness and participation in maintaining environmental cleanliness through activities such as waste management counseling, the creation of segregated trash bins, environmental campaigns, and assistance in forming environmental cadres. Residents have started to get used to sorting waste at home and actively participating in communal efforts to clean village roads. Support from the village head and village officials has strengthened the sustainability of the program, making this activity not only temporary but also a concrete step towards a cleaner and more sustainable environment.